Experimental Evaluation of the Dose-Dependent Pharmacological Effects of Metformin on Glycemic Control, Oxidative Stress, and Insulin Sensitivity in Streptozotocin-Induced Diabetic Wistar Rats - Soni Singh; Anil Kumar; Komal Yadav; Sundarajan R; S Vasiha Anjum; Lalatendu Mohanty; Renuka Mahajan; Falgun Gunvantray Dhabaliya; Raghav Dixit (The Bioscan, 2026)
Background Diabetes Mellitus is a chronic metabolic condition characterized by persistent hyperglycemia, insulin resistance, and increased oxidative stress, leading to severe systemic complications. Metformin is widely used as a first-line therapy; however, its dose-dependent pharmacological effects on glycemic control, oxidative stress, and insulin sensitivity require further investigation. Objective To evaluate the dose-dependent effects of metformin on glycemic control, oxidative stress, and insulin sensitivity in Streptozotocin-induced diabetic Wistar rats. Methods Experimental diabetes was induced in Wistar rats using a single intraperitoneal injection of streptozotocin (50 mg/kg). Animals were divided into five groups (n = 6–8): normal control, diabetic control, and three metformin-treated groups (100, 200, and 300 mg/kg). Metformin was administered orally for 28 days. Key parameters assessed included fasting blood glucose, oral glucose tolerance test (OGTT), HbA1c, serum insulin levels, HOMA-IR index, and oxidative stress markers (MDA, SOD, CAT, and GSH). Histopathological examination of pancreatic tissue was also performed. Statistical analysis was conducted using one-way ANOVA followed by Tukey’s post hoc test. Results Metformin treatment significantly improved glycemic control in a dose-dependent manner, as evidenced by reductions in fasting blood glucose, improved OGTT response, and decreased HbA1c levels (p < 0.05–0.001). Insulin sensitivity was enhanced, with increased serum insulin levels and reduced HOMA-IR values. Oxidative stress was markedly reduced, demonstrated by decreased MDA levels and increased antioxidant enzyme activities (SOD, CAT, GSH). Histopathological analysis revealed dose-dependent protection and regeneration of pancreatic β-cells, with the high- dose group showing near-normal architecture. Conclusion Metformin exhibits significant dose-dependent antidiabetic and antioxidant effects in streptozotocin-induced diabetic rats. Higher doses provide superior improvements in glycemic control, insulin sensitivity, and oxidative stress. These findings support the importance of dose optimization in enhancing the therapeutic efficacy of metformin and warrant further clinical investigations for translational application.